Intervensi Art Therapy untuk Meningkatkan Self Esteem pada Pasien Dewasa Skizofrenia Paranoid - Harniati, Yunia; Dinni, Siti Muthia (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2024)
Schizophrenia is a psychotic disorder that arises from vulnerability or predisposition to developmental disorders and is also usually genetic. In overcoming paranoid schizophrenia, it can be done with art therapy. This study aims to determine the effectiveness of art therapy to increase self-esteem in paranoid schizophrenia patients. The research subject was a patient of "X" Mental Hospital in Central Java with paranoid schizophrenia disorder aged 48 years male, who showed a decrease in self-esteem after being discharged from the hospital. The data collection methods used were observation, interviews, and psychological tests. Psychological tests were given to the subject in the form of cognitive tests, namely SPM (Standard Progressive Matrices), Graphic test, Wartegg test, SSCT test (Sack's Sentence Completion Test), and DASS test (Depression Anxiety Stress Scales). This study used one research subject with a single case Pre-test Post-test Design. Researchers use art therapy to explore the subject's unconsciousness to the surface. In the end, the subject realized what was happening to him with the catharsis process and formed thoughts and feelings that were difficult to express. This helps the subject reduce the tension felt and increases self-esteem. Art therapy is given individually for five meetings. The results showed that the effectiveness of art therapy boosted self-esteem in paranoid schizophrenia patients. After being given the intervention, the subject showed changes from before and after being given the intervention. The subject realized that there were some things that he could not control. The subject also learned that there would be a way out from all the trials and events, even though it took time, so the subject began to open up to others, especially his wife.